Utilisation of bacterial (Rubrivivax gelatinosus) biomass for egg yolk pigmentation - Polonio, Lorrayne Bernegossi [UNESP]; Giglio Ponsano, Elisa Helena [UNESP]; Pinto, Marcos Franke [UNESP]; Garcia-Neto, Manoel [UNESP] (CSIRO Publishing, 2010)
The effects of Rubrivivax gelatinosus biomass inclusion in diets of Dekalb White laying hens were assessed. The traits studied were yolk colour, consumer preference and hepatic and renal function. Broken-line regression was used to assess the biomass requirements for yolk colour attributes. Hens were fed one of six experimental diets formulated with the bacterial biomass at 0 (control), 1.5, 3.0, 4.5, 6.0 and 7.5 g/kg into a corn-soybean meal basal feed for 30 days. All tested concentrations of the biomass caused darkening and increased redness of yolks but did not affect yellowness. The yolk colour most preferred by an untrained panel was achieved by inclusion of a dietary biomass of 4.5 g/kg, the same as the requirement for maximum redness. Biochemical and histological analysis indicated an absence of deleterious effects of the product on liver and kidney functions during the study period. These results indicate that R. gelatinosus biomass can be used to increase red yolk pigmentation.